The potential for commercial hay production in Kenya - Dijk, Suzanne van; Wilkes, Andreas; Odhong’, Charles (2018)
Feed and fodder production, supply and feeding practices are among the most important constraints on the development of the Kenyan dairy industry. Increasing fodder supply, supported by advice provided to farmers on feed ration balancing has great potential to enable farmers to increase on- farm productivity, reduce the dip in milk production during the dry season, increase incomes and reduce GHG emission intensity. With a current large hay deficit in the country as well as financially viable business models, great potential exists for commercial hay value chains. A lack of machinery and storage facilities as well as knowledge of agronomic measures to increase hay yields and quality currently hinder hay growers to fully exploit market potential. Because commercial hay production is a recent development, financial institutions lack experience with and knowledge of the sub-sector. Technical assistance to both financial institutions and hay growers (for record keeping, financial management) could help overcome these barriers and support hay growers to make the required investments in machinery and storage facilities.